Imaging of Biliary Involvement in Sarcoidosis: Computed Tomography, Magnetic Resonance Cholangiopancreatography, and Gadolinium Ethoxybenzyl Diethylenetriamine Pentaacetic Acid-Enhanced Magnetic Resonance Imaging Findings - Matteo Renzulli; Mario Casavola; Alberto Foà; Carmine Pizzi; Rita Golfieri (Tomography, 2021)
Sarcoidosis is a multisystem disease usually affecting the chest, hilar lymph nodes, and lungs, but can potentially involve any organ; therefore, its clinical presentation may vary. Hepatobiliary involvement is rare, and typically asymptomatic; however, it can lead to cirrhosis, and may require liver transplantation. In this report, we present a rare case of a patient affected by sarcoidosis with hepatobiliary involvement. He presented to our hospital complaining of dyspnea triggered by moderate efforts and oppressive thoracic discomfort. Chest X-ray showed multiple bilateral nodular opacities and enlargement of both hilar regions, confirmed by a subsequent total-body computed tomography scan and positron emission tomography, which also revealed cardiac, splenic, and hepatic involvement. Liver function was studied via gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance imaging, and magnetic resonance cholangiopancreatography (MRCP) was also performed. The diagnosis of sarcoidosis was finally achieved via liver biopsy, revealing non-necrotizing granulomas in the periportal space. The patient was treated with prednisone per os, with regression of all lesions at all levels. Although other cases of biliary sarcoidosis have been described, this report provides a complete image set of Gd-EOB-DTPA-enhanced magnetic resonance and MRCP images that is lacking in the English literature, and which may be useful for diagnosis.